The The Influence of Exchange Rate, Export, Import and Economic Growth on Turkish Inflation - Maharani, Risky Amelia; Arifin, Zaenal (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
This study aims to analyze the effect of exchange rate, exports, imports, and economic growth on Turkey's inflation over 1992-2022. Using annual time series data, this study applies the multiple linear regression method to identify these variables' relationships. Before conducting the regression analysis, a stationarity test is performed using the second difference method to ensure that the data does not have significant trends or seasonal patterns. The results show that the exchange rate positively and significantly affects inflation in Turkey. Exports and economic growth show a positive but insignificant effect, while imports negatively and significantly affect inflation. These findings indicate that fluctuations in the exchange rate and import volume are more influential in determining the inflation rate in Turkey than exports and economic growth. This study concludes that an effective monetary policy to control inflation in Turkey should consider exchange rate management and import control. Other factors, such as exports and economic growth, may have less influence on inflation during the studied period.